Studies of radon in Ireland : outdoor levels, detector intercomparison and school remediation methods - Gunning, Gillian A. (Trinity College (Dublin, Ireland). School of Physics, 2016)
Although Ireland has a comprehensive radon strategy in place and an active research community, the rate of testing is still low. The work in this thesis aims to reduce knowledge gaps by making outdoor radon measurements, aid the introduction of radon testing for conveyancing purposes and evaluate the necessity of remediation follow-up programmes. Long term outdoor radon measurements across Ireland were recorded using CR-39 track etch detectors. For this study, a measurement protocol was designed that was optimised for the relatively low radon concentrations expected outdoors. This protocol included pre-etching the detectors before exposure to allow radon tracks to be more easily distinguished from background. The average outdoor radon concentration for the Republic of Ireland was found to be 5.6 ± 0.7 Bq/m3 which equates to an annual dose of 0.05 mSv to the Irish population. Prior to this study, a value of 6 Bq/m3 was estimated to be the outdoor concentration for Ireland and this value was extrapolated from a Q-Q (quantile-quantile) plot of indoor log-normal radon concentration. The correlation of this theoretical value with the measured value from this study verifies that this method of extrapolating is correct, and should be considered to predict the outdoor concentration in other countries where indoor data exists. A statistically significant difference between inland and coastal radon concentrations was evident but no difference between mean radon concentrations on the east coast and those on the west coast was observed. Currently in Ireland radon testing is not a requirement for conveyancing or for dwelling rental and one perceived obstacle for its inclusion is the recommended 3 month measurement period. A comparison study was therefore conducted of seven different types of radon detectors (Atmos 12 dpx, RAD7, RStone, Sun Nuclear 1028, Ramon 2.2, Canary and CR-39) for exposure periods of 1, 2, 3 and 4 weeks. The comparison was performed under two conditions: (a) in a purpose-built radon chamber with an average radon concentration of 2,560 Bq/m3 (b) in a home environment with a radon concentration of 57 Bq/m3, in both cases measured by the reference detector (Atmos 12 dpx) with a ±10% uncertainty range. In (a) 5 out of 8 detectors recorded radon concentrations within the Atmos uncertainty range and all detectors recorded within ±15%; in (b) 3 out of 9 detectors recorded within the Atmos uncertainty range and 6 out of 9 measured within ±20%, for a 4 week measurement. The results from this study show that radon surveys can be conducted for shorter periods than the recommended 3 months where a rapid indication is needed of whether the radon concentration is above the reference level, such as when assessing the concentration during and after remediation work. In Ireland, during the years 1998 to 2004 the Department of Education and Skills (DES), with the assistance and guidance of the Environmental Protection Agency - Office of Radiological Protection (EPA-ORP), undertook the National Survey of Radon in Irish Schools. This was a large scale project to measure the radon levels in primary and post-primary schools in Ireland. Rooms which were found to have a concentration greater than 200 Bq/m3 had some form of remediation installed to reduce the radon concentration. To determine the durability of the remediation methods and study the importance of structured follow-up programs, radon re-tests were performed in 16 of the schools that had some form of remediation implemented. The results showed that 26% of the rooms had risen to above the reference level of 200 Bq/m3 again and 10% to above 400 Bq/m3 , leading to the prediction that currently 790 rooms are > 200 Bq/m3 and 80 rooms are > 400 Bq/m3 in the 3,826 schools originally tested. Through case studies and a questionnaire, the radon awareness in schools was observed to be correlated to an ability to maintain radon concentrations below the reference level. Only 15% of the schools in this study regularly checked or serviced their remediation systems. Testing for radon is crucial in indicating where remediation methods are less effective or have failed.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin